INFORMAL EDUCATION AS AN ALTERNATIVE FOR OBTAINING QUALITY HIGHER EDUCATION IN UKRAINE IN MODERN CONDITIONS - Shalova, Natalia; Korbut, Oksana; Stavytska, Iryna (Sworld-Us Conference proceedings, 2023)
The trends in the development of informal education as an alternative way of obtaining higher education in Ukraine in modern conditions are analyzed. The general types of informal education, its advantages, disadvantages and peculiarities of recognition o